Summary of wireless indoor positioning technology in industry Internet - HANGE C; Weijie LENG (物联网学报)
With the rapid development of industry in China,the manufacture needs technological change,and smart factory becomes the key during the changes.Smart factory needs the indoor positioning technology to position the staffs,the materials,the equipment and the vehicles precisely.The requirement of wireless positioning technology was analyzed in industry at first,then the multiple wireless positioning technologies were contrasted,and the development trend of wireless positioning technology in industry was proposed at last.